ANALYSIS OF THE EFFECTIVENESS OF THE GOVERNMENT'S ASSISTANCE FOR MICRO BUSINESSES ON CULINARY SECTOR MSMES IN THE MASS OF THE COVID-19 VIRUS PANDEMIC IN SAWAH BESAR DISTRICT, CENTRAL JAKARTA - Mochamad Arief Iskandar; Sugeng Santoso; Ridho Sunella Putra; Gita Thessa Lonika Putri; Reza Wahyu Perdana; Purna Irawan (Journal of Economics, Business, and Government Challenges, 2021)
The economic chaos that has occurred in almost all parts of the world has an unstable global economic condition due to the Corona Virus. In the midst of the onslaught of the global economic crisis, small, medium and large businesses are all affected by the Corona Virus outbreak that has attacked the whole world. Since the Corona Virus attacked the entire world, many MSMEs have experienced many obstacles and obstacles, especially in terms of capital. The government is trying to solve this problem by launching a financing program for MSMEs and cooperatives, namely Assistance for Micro Businesses (BPUM). The purpose of this study was to determine the effectiveness of Assistance for Micro Business Actors (BPUM) in increasing the income of MSMEs in Sawah Besar District, Central Jakarta. The data collection process was carried out by giving a number of questionnaires to several traders selling around the Sawah Besar District, totaling 10 respondents. This research approach uses quantitative descriptive methods. The results showed that the impact of the Covid-19 pandemic was that the MSME assistance program had a positive impact on MSME income in Sawah Besar District, Central Jakarta. So it is advisable for the government to continue to run the Assistance for Micro Businesses (BPUM) program to help MSME capital problems. The results showed that the impact of the Covid-19 pandemic was that the MSME assistance program had a positive impact on MSME income in Sawah Besar District, Central Jakarta. So it is advisable for the government to continue to run the Assistance for Micro Businesses (BPUM) program to help MSME capital problems. The results showed that the impact of the Covid-19 pandemic was that the MSME assistance program had a positive impact on MSME income in Sawah Besar District, Central Jakarta. So it is advisable for the government to continue to run the Assistance for Micro Businesses (BPUM) program to help MSME capital problems.